Digital Interventions for Psychological Well-being in University Students: Systematic Review and Meta-analysis - Madeleine Ferrari; Stephanie Allan; Chelsea Arnold; Dina Eleftheriadis; Mario Alvarez-Jimenez; Andrew Gumley; John F Gleeson (JMIR Publications, 2022)
BackgroundLife at university provides important opportunities for personal growth; however, this developmental phase also coincides with the peak period of risk for the onset of mental health disorders. In addition, specific university lifestyle factors, including impaired sleep and academic and financial stress, are known to exacerbate psychological distress in students. As a result, university students have been identified as a vulnerable population who often experience significant barriers to accessing psychological treatment. Digital psychological interventions are emerging as a promising solution for this population, but their effectiveness remains unclear. ObjectiveThis systematic review and meta-analysis aimed to assess digital interventions targeting psychological well-being among university students. MethodsDatabase searches were conducted on December 2, 2021, via Embase, MEDLINE, PsycINFO, and Web of Science. ResultsA total of 13 eligible studies were identified, 10 (77%) of which were included in the meta-analysis. Mean pre-post effect sizes indicated that such interventions led to small and significant improvement in psychological well-being (Hedges g=0.32, 95% CI 0.23-0.4; P<.001). These effects remained, albeit smaller, when studies that included a wait-list control group were excluded (Hedges g=0.22, 95% CI 0.08-0.35; P=.002). An analysis of acceptance and commitment therapy approaches revealed small and significant effects (k=6; Hedges g=0.35, 95% CI 0.25-0.45; P<.001). ConclusionsDigital psychological interventions hold considerable promise for university students, although features that optimize service delivery and outcomes require further assessment. Trial RegistrationPROSPERO CRD42020196654; https:/www.crd.york.ac.uk/prospero/display_record.php?RecordID=196654